EGR1 Is Implicated in Right Ventricular Cardiac Remodeling Associated with Pulmonary Hypertension - Maria Laggner; Felicitas Oberndorfer; Bahar Golabi; Jonas Bauer; Andreas Zuckermann; Philipp Hacker; Irene Lang; Nika Skoro-Sajer; Christian Gerges; Shahrokh Taghavi; Peter Jaksch; Michael Mildner; et al. (Biology, 2022)
Background: Pulmonary hypertension (PH) is a vasoconstrictive disease characterized by elevated mean pulmonary arterial pressure (mPAP) at rest. Idiopathic pulmonary arterial hypertension (iPAH) and chronic thromboembolic pulmonary hypertension (CTEPH) represent two distinct subtypes of PH. Persisting PH leads to right ventricular (RV) hypertrophy, heart failure, and death. RV performance predicts survival and surgical interventions re-establishing physiological mPAP reverse cardiac remodeling. Nonetheless, a considerable number of PH patients are deemed inoperable. The underlying mechanism(s) governing cardiac regeneration, however, remain largely elusive. Methods: In a longitudinal approach, we profiled the transcriptional landscapes of hypertrophic RVs and recovered hearts 3 months after surgery of iPAH and CTEPH patients. Results: Genes associated with cellular responses to inflammatory stimuli and metal ions were downregulated, and cardiac muscle tissue development was induced in iPAH after recovery. In CTEPH patients, genes related to muscle cell development were decreased, and genes governing cardiac conduction were upregulated in RVs following regeneration. Intriguingly, early growth response 1 (EGR1), a profibrotic regulator, was identified as a major transcription factor of hypertrophic RVs in iPAH and CTEPH. A histological assessment confirmed our biocomputational results, and suggested a pivotal role for EGR1 in RV vasculopathy. Conclusion: Our findings improved our understanding of the molecular events driving reverse cardiac remodeling following surgery. EGR1 might represent a promising candidate for targeted therapy of PH patients not eligible for surgical treatment.